The evolving role of the Rhema Movement in the South African public square - Oosthuizen, Marius (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The position of the Rhema Movement on law and religion in South Africa, and religious freedom in particular, can be understood by assessing their changing role in the public square. Underlying their role is the view that, public engagement and social justice are forms of religious expression, embarked upon within the robust religious freedom of contemporary South Africa. The impetus for involvement in the political landscape of South Africa, by the Rhema Bible Church, a Charismatic Pentecostal Christian Church, and its’ leader, Pastor Ray McCauley, has been widely speculated over in the media. It is the premise of this paper that by assessing the Rhema Movement’s changing role in the public square in recent decades, as well as the theological and philosophical basis for such engagement, the position of the Rhema Movement on law and religion, and religious freedom in particular, can be understood. Underlying their actions, Marius Oosthuizen argues herein, is their stance that public engagement and social justice are forms of religious expression, upon which they seek to embark within the robust religious freedom afforded them by the constitutional dispensation of contemporary South Africa.